Risk factors of overuse shoulder injuries in overhead athletes: A systematic review - Tooth, C.; Gofflot, A.; Schwartz, C.; Croisier, J.-L.; Beaudart, C.; Bruyère, O.; Forthomme, B. (Sports Health: A Multidisciplinary Approach, 2020)
Context: Shoulder injuries are highly prevalent in sports involving the upper extremity. Some risk factors have been identified in the literature, but consensus is still lacking.